Modern Architecture and Modern Furniture - Mácêl, Otakar (Docomomo Journal, 2012)
Modern architecture and Modern furniture originated almost during the same period of time. Modern architects needed furniture compatible with their architecture and because it was not available on the market, architects had to design it themselves. This does not only apply for the period between 1920 and 1940, as other ambitious architectures had tried before to present their buildings as a unit both on the inside and on the outside. For example one can think of projects by Berlage, Gaudí, Mackintosh or Horta or the architectures of Czech Cubism and the Amsterdam School. This phenomenon originated in the 19th century and the furniture designs were usually developed for the architect’s own building designs and later offered to the broader consumer market, sometimes through specialized companies. This is the reason for which an agreement between the architect and the commissioner was needed, something which was not always taken for granted.